PENGEMBANGAN INDIKATOR 4 C’s YANG SELARAS DENGAN KURIKULUM 2013 PADA MATA PELAJARAN MATEMATIKA SMP/MTs KELAS IX SEMESTER 1 - Indriawati, Syahdinar; Sunardi, Sunardi; Kurniati, Dian (Kadikma, 2017)
Abstract. This research is aimed to produce 4C’s indicators that are synchronal with 2013 curriculum on 1st semester of 9th grade junior high school’s mathematic subject. According to P21, 4C’s abilities are critical thinking, creative, communication, and collaboration. 9th grade material on the first semester consists of 3 chapters; quadratic and square root of number, quadratic equation, and quadratic function. The process of developing indicators in this study has the advantage that the indicators developed also relate to the skills of learners in terms of mastering technology, information and media. So in the 21st century students are expected to improve the ability of high-level thinking as well as technology mastering skills, so that students are able to develop in a competitive future. The research design used in this research is Plomp development model that has been modified and consists of 4 phase; preliminary investigation, design, realization/construction, test, evaluation, and revision. The instrument used in this research is 4C’s indicators validation that is synchronic with 2013 curriculum. The data collection process is conducted by using product validity test to some validates. The result of this 4C’s indicators development has 3,89 on validity result coefficient which is accepted in valid interpretation category. Therefore, the development of 4C’S indicators synchronize with 2013 curriculum on 1st semester of 9th grade junior high school’s mathematic subject has been qualified valid criterion. Keywords: Plomp development, 4C’s indicators, 2013 curriculum